Step by step [large type] - Calvert, Candace, 1950- (Calvert, Candace, 1950- Crisis team, 2016)
Three years after a tragic accident left her a widow, ER nurse Taylor Cabot is determined to move on, checking off one item after another on her survival list. Her relationship with a handsome plastic surgeon even gives her hope for the last item: "fall in love again." At least until crisis chaplain Seth Donovan steps back into her life, reawakening unanswered questions about her husband's death. And nothing prepares Seth for the feelings that arise when he sees Taylor again ... and sees her moving on with another man.